2016
DOI: 10.1142/s0129183116500091
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of traffic car accidents at a single lane roundabout

Abstract: In this paper, using the Nagel-Schreckenberg model, we numerically investigate the probability P ac of entering/circulating car accidents to occur at single-lane roundabout under the expanded open boundary. The roundabout consists of N on-ramps (respectively, o®-ramps). The boundary is controlled by the injecting rates 1 ; 2 and the extracting rate . The simulation results show that, depending on the injecting rates, the car accidents are more likely to happen when the capacity of the rotary is set to its maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The topics studied have included study road traffic dynamics in roundabouts [69], and the study of probability of road accidents [70,71]. The current publication focuses on developing a model for multi-lane roundabouts.…”
Section: Roundabout Cellular Automaton (Ca) Modelsmentioning
confidence: 99%
“…The topics studied have included study road traffic dynamics in roundabouts [69], and the study of probability of road accidents [70,71]. The current publication focuses on developing a model for multi-lane roundabouts.…”
Section: Roundabout Cellular Automaton (Ca) Modelsmentioning
confidence: 99%
“…Based on the observation of different transitions, including the transition between free-flowing and gridlock and bottleneck and gridlock, the author has identified that the gridlock can be taken as an extreme limit of bottleneck. Cellular automata models have been also used to study the probability of car accidents for various traffic scenarios [13][14][15]. The first CA model including dangerous situations (accident) have been proposed by Boccara et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…The author discusses the effect of these conditions on the probability of traffic accidents. In [15], the authors have studied the probability of entering/circulating car accidents to occur at single-lane roundabout when the incoming vehicles ignore the priority rules.…”
Section: Introductionmentioning
confidence: 99%
“…Many 3 observed traffic phenomenon have been successfully described by computer simulation with various models, e.g. car 4 following, Fluid-dynamical method, and Cellular automaton (CA) [1][2][3][4][5][6][7][8][9][10][11][12][13]. This later has been adopted extremely and well 5 received as a good tool to study the traffic and/or pedestrian dynamics [8][9][10][11][12]14].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many studies have 7 examined the pedestrian flow and its effect on vehicular traffic [15][16][17][18][19][20][21][22][23][24]. Feng et al [15] proposed a cellular automata model 8 to evaluate walkers' facilities before its implementation, Zhuang and Wu [16] developed a model of pedestrian crossing 9 paths at unmarked roadways to better understand pedestrian behaviors, Yannis et al [17] studied walkers' gap acceptance 10 for mid-block road crossing in urban areas, Xie et al [18] investigated the characteristics of the traffic flow on a road with 11 a signalized crosswalk in the framework of CA model, Zhang et al [19] proposed a cellular automata model to study the Furthermore, we analyze how the location of the crosswalk and the driver cooperative behavior can influence the dynamic 3 characteristics of pedestrian and vehicle flux. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%